Zama Zama Mining as Necro-Extractivism: A Thematic Analysis of Print and Social Media Discourses on the Stilfontein Mining Tragedy (November 2024 – March 2025) - Thaathaa, Likhapha (Stellenbosch : Stellenbosch University, 2026)
Thesis (MA)--Stellenbosch University, 2026.